2022
DOI: 10.36660/ijcs.20200323
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Associated Factors in Atherosclerotic Cardiovascular Disease Patients with and without Diabetes at a Specialized Outpatient Clinic in the City of Pelotas, Brazil

Abstract: Background: In most cases, atherosclerotic cardiovascular disease (ACVD) is preventable through primary prevention and control of traditional risk factors, such as smoking cessation, regular physical activity, and adherence to healthy dietary patterns. The assessment of diet quality of ACVD patients would be important for a dietary intervention.Objectives: This study aimed to evaluate diet quality of ACVD patients and its association with clinical conditions. Methods: This cross-sectional study was nested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In this issue of the International Journal of Cardiovascular Sciences, Dobke et al, 11 in a cross-sectional study using data from a randomized clinical trial entitled "Efeito do Programa Alimentar Brasileiro Cardioprotetor (DICA Br)", 12 evaluated diet quality of patients with atherosclerotic cardiovascular diseaseCVD, applying the Revised Diet Quality Index (IQD-R). After analyzing data from 80 patients from Pelotas, Brazil, they found that the items "whole grains," "dark green and orange vegetables," "total fruits," and "whole fruits" had the lowest IQD-R scores, while the items "meats, eggs, and pulses" and "total cereals" had the highest.…”
mentioning
confidence: 99%
“…In this issue of the International Journal of Cardiovascular Sciences, Dobke et al, 11 in a cross-sectional study using data from a randomized clinical trial entitled "Efeito do Programa Alimentar Brasileiro Cardioprotetor (DICA Br)", 12 evaluated diet quality of patients with atherosclerotic cardiovascular diseaseCVD, applying the Revised Diet Quality Index (IQD-R). After analyzing data from 80 patients from Pelotas, Brazil, they found that the items "whole grains," "dark green and orange vegetables," "total fruits," and "whole fruits" had the lowest IQD-R scores, while the items "meats, eggs, and pulses" and "total cereals" had the highest.…”
mentioning
confidence: 99%